PENGEMBANGAN TATA RIAS KARAKTER TURONGGO YAKSO DALAM LOMBA VIDEO TUTORIAL INOVATIF DAN IDE BISNIS - Kurnia; Octaverina Kecvara Pritasari; Agus Wiyono; Nia Kusstianti (Program Studi Pendidikan Tata Rias, 2025)
Turonggo Yakso as one of the cultural diversities in the form of traditional art that fascinates by offering not only entertainment but also a window into the richness of Indonesian culture and historical heritage. The results of the study based on the video tutorial competition and creative business ideas in the field of make-up aim to provide a positive contribution in introducing Indonesian culture, especially the art of make-up in the Turonggo Yakso dance, both nationally and internationally. The research and development (R&D) approach was used with the 4D model (define, design, develop, disseminate). The results of the study showed that the make-up that was developed was able to create a stunning visual appearance while maintaining cultural values. The resulting video tutorial won 1st place nationally, demonstrating its effectiveness in preserving culture and inspiring the community and students to be more active in preserving traditional arts through digital platforms.